“A Calamity From Which No Relief Can Be Expected”: Empire, Authority, and Civilian Responses to the French Occupation of Newfoundland, June-September 1762 - Humphries, Mark (Acadiensis, 2014)
As customary socio-economic relationships between the inhabitants of Newfoundland broke down, normal patterns of exchange ceased to function during the 18th century. Because the island was a contested space – even in peacetime – existing economic and social connections enabled civilians to choose to resist, collaborate, or flee. While some were ruined, others maintained the status quo, and some even profited from new opportunities. In the end, re-capturing St. John’s was less important for pressing English claims in the area than reconstructing the economy and asserting control over the movement of people and trade within overlapping French and English transatlantic worlds.